Analysis of the roots and contradictions of secularism in Turkey - borhan salimi (رهیافتهای سیاسی و بین المللی)
The present paper is aimed at investigating the intellectual – historical roots of institutional secularization of the Turkish government, and fundamental characteristics and contradictions of the Turkish secularism model (known as Laiklik) during its establishment period. Later on, these contradictions caused major challenges in the Turkish politics, keeping the religion – government gap still an active political issue. Despite the officiality of the Laiklik and the official secular rhetoric, the government’s authoritative interventions into religious affairs, nationalization of Islam, and failure to preserve the neutrality of the government in practice (regarding different religions and sects) are among the most important characteristics of the Turkish secularism during its establishment period. These three contradicting characteristics are among the most important distinctions between this particular model of secularism and the western models of secularism.Considering equal dignity for people with different religious and non-religious beliefs and ensuring conscience – religion freedom have been among the most basic objectives of the secularism. The principle of non-interference of the government in religious affairs and the principle of neutrality are basic instruments for realizing such an objective. In the Turkish model, however, from the early stages of establishment of the secularism (Ataturk Administration), the objectives were pretty ambiguous. During this stage, the secular politics was based on political authoritarianism, extreme ethnic nationalism, and authoritative modernization, of which the secularization was only a part. Accordingly, this model of secularism possessed particular features and contradictions that have remained unresolved till today